2014
DOI: 10.1007/s10120-014-0349-z
|View full text |Cite
|
Sign up to set email alerts
|

The course of gastric cancer following surgery is associated with genetic variations of the interleukin-1 receptor antagonist and interleukin-1β

Abstract: Background Inflammation, especially the cytokine response of the IL-1 family, has been shown to influence susceptibility to gastric cancer. In addition, several other pro-inflammatory cytokines have been demonstrated to influence metastasis and resistance to chemotherapy. Therefore, genetic variations within these genes may not only affect susceptibility but also influence the outcome of gastric cancer patients. A limited number of studies showed indeed an association of IL-1b and IL-1RN variations with surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Studies of familial clustering, ethnic differences and polymorphisms of inflammation-related genes have provided evidence that host genetic factors play a pivotal role in the pathogenesis of gastric cancer [9,10]. The TNF-␣ codifies a potent immunomodulator and pro-inflammatory cytokine that mediates diverse pathological processes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of familial clustering, ethnic differences and polymorphisms of inflammation-related genes have provided evidence that host genetic factors play a pivotal role in the pathogenesis of gastric cancer [9,10]. The TNF-␣ codifies a potent immunomodulator and pro-inflammatory cytokine that mediates diverse pathological processes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of inflammation-related genes have provided evidence that host genetic factors play a pivotal role in the pathogenesis of GC [5,6]. TNF-α is a potent immunomodulator and pro-inflammatory cytokine that mediates diverse pathological processes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that GC susceptibility genes, combined with environmental factors, may play an important role in the development of cancer. In 2000, El-Omar [ 7 ] first reported that IL-1β gene polymorphism increased the risk of GC onset, a finding subsequently confirmed by later studies [ 8 10 ]. The IL-1β gene is mapped to chromosome 2q14 and has 3 single-nucleotide polymorphisms (SNPs): 31 T/C, 511 C/T, and 3954 C/T.…”
Section: Introductionmentioning
confidence: 93%